Respiratory infections as vascular triggers: self-controlled case series analysis of linked Scottish data. (23rd February 2017) - Warren-Gash, Charlotte; Blackburn, Ruth; Whitaker, Heather; Hayward, Andrew
Abstract: Background: Infections can trigger acute vascular events but the differential effect of specific respiratory pathogens is unknown. We aimed to quantify the association between laboratory-confirmed respiratory bacterial or viral infections and first myocardial infarction or stroke to inform intervention development and targeting. Methods: Scottish Morbidity Record data on first myocardial infarction or stroke (International Classification of Diseases, 10th revision, codes) were linked to records of Streptococcus pneumoniae, influenza, rhinovirus, parainfluenza, respiratory syncytial virus, or human metapneumovirus from the Electronic Communication of Surveillance in Scotland (National Services Scotland) dataset on individuals aged 40 years or older from Jan 1, 2004, to Dec 31, 2014. We analysed incidence ratios for myocardial infarction or stroke in the 28 days after infection compared with baseline using self-controlled case series. Findings: There were 1227 individuals with myocardial infarction (751 men [61%]) and 762 with stroke (392 men [51%]). Median age was 68 years (IQR 59–77). The relative incidence of myocardial infarction was markedly raised in the first 1–3 days after both bacterial and viral infections (incidence ratio 5·98, 95% CI 2·47–14·4 [p<0·0001] and 5·59, 1·77–17·6 [p=0·003], respectively) and persisted for about 1 week. For stroke, the respective relative incidence after respiratory infection was even higher for days 1–3 (12·3, 5·48–27·7 [p<0·0001] and 6·79, 1·67–27·50 [p=0·007]). Elevated stroke risks after both bacterial and viral infections persisted to 28 days (p<0·0001). Interpretation: Our findings suggest that respiratory bacterial and viral infections act as vascular triggers. For stroke, the incidence ratio remained elevated a month after the date of respiratory sampling but for myocardial infarction the raised incidence ratio appeared to be more transient, suggesting potentially different mechanisms. This study highlights the need to ensure adequate uptake of influenza and pneumococcal vaccines as well as appropriate treatment during infections to reduce vascular risk. Funding: Academy of Medical Sciences.